Analisis Kinerja Karyawan Ditinjau Dari Manajemen Talenta Dan Manajemen Pengetahuan Dengan Mediasi Komitmen Organisasi Pada PT. Transco Pratama CRF Sungai Betung Dharmasraya - Esy Avriani; Ramdani Bayu Putra; Amrefri Amrefri (JURNAL PUNDI, 2021)
The purpose of this study was to determine how much influence Talent Management, Knowledge Management has on Organizational Commitment, and how much influence Talent Management, Knowledge Management, and Organizational Commitment have on Employee Performance at PT. Transco Pratama Crf Sungai Betung Dharmasraya. The data analysis method used a questionnaire, with a sample of 70 respondents. The data analysis method used is path analysis. Based on the results of the research, it shows that Talent Management and Knowledge Management has a positive and significant effect on Organizational Commitment. Talent Management, Knowledge Management and Organizational Commitment has a positive and significant effect on Employee Performance. Organizational Commitment mediates Talent Management on Employee Performance, and Organizational Commitment mediates Knowledge Management on Employee Performance.